Model Antroplogis Stephen B. Vans : Kajian Teologis Kontekstual Pelaksanaan Adat Masikka’ Dalam Acara Pemakaman Di Desa Ranta Damai - Cindy Natalia Salinding; Gita Aurelia Tikara; Mercrys Ko’si Pongda’ka (DA'AT : Jurnal Teologi Kristen, 2023)
Masikka' is a poem that is sung or sung by the Customary Stakeholders (the leader of the poem sings first and then followed by other singers) when a member of the nobility (Parengnge' and Tomatua) dies. To get the meaning of the poem and the theological values ​​contained in Masikka', the two authors used qualitative methods to find information related to Masikka culture and went directly to conducting interviews in Rante Peace. Masikka' is done to give final respect to people who have died for the services or influences that have been carried out during their life to the Rante Balla community and also there is an understanding that this culture is carried out as a provision for that person to go to a new world (another world). In this article the author uses a qualitative method using the Anthropological model approach of Stpehen B. Vans. The purpose of this article is to examine theologically the implementation of the Masikka ritual at a funeral in the Peace Chain Village from the perspective of Stephen B, Vans' anthropological model.